Logic Conflicts in Community-Based Palliative Care. (4th May 2021) - Vijay, Devi; Whitelaw, Sandy; Clark, David
Abstract: Community-based palliative care services and their integration with public health systems are of considerable contemporary interest. However, the conflicts that emerge in such a complex organizational field comprising multiple stakeholders with diverse interests remain under-examined. Our analysis of community-based palliative care in Kerala identifies four 'logic conflicts' that indicate competing frames of reference in an organizational field. These conflicts shape decision-making and coordination and manifest as: 1) professional versus community logics, 2) centralized versus decentralized governance logics, 3) generalist versus specialist care logics, 4) charity versus rights-based logics . We also identify two mechanisms – forming coalitions and fostering plurality – by which actors manage these conflicting logics. We discuss contributions to public health palliative care conversations and implications for nurturing and sustaining care communities.